Notes respecting Coins found in the Walls of an Old House in the Town of Ayr; and at the Village of Newstead, Roxburghshire (Proceedings of the Society of Antiquaries of Scotland, 1864)
Two lists of coins found in the walls of old buildings, one in Ayr and one near Melrose, that were later acquired by the Treasure Trove.